Biological control of Magnaporthe oryzae using natively isolated Bacillus subtilis G5 from Oryza officinalis roots - Lei, Ling-Yun; Xiong, Zi-Xuan; Li, Jin-Lu; Yang, De-Zheng; Li, Liu; Chen, Ling; Zhong, Qiao-Fang; Yin, Fu-You; Li, Rong-Xin; Cheng, Zai-Quan; Xiao, Su-Qin (Frontiers in Microbiology, 2023)
Rice blast, caused by Magnaprthe oryzae, is a major threat to global rice production causing significant crop losses and impacting grain quality. The annual loss of rice production due to this disease ranges from 10-30%. The use of biologically controlled strains, instead of chemical pesticides, to control plant diseases has become a research hotspot. In this study, an antagonistic endophytic bacterial strain was isolated from the roots of Oryza Officinalis using traditional isolation and culture methods. A phylogenetic tree based on 16S RNA and whole-genome sequencing identified isolate G5 as a strain of Bacillus subtilis. This isolate displayed strong antagonistic effects against different physiological strains of M. oryzae. After co-culture in LB medium for 7 d, the inhibition rate on the mycelial growth of four strains of M. oryzae, ZB15, WH97, Guy11, and T-39800E, were 98.07 ± 0.0034%, 98.59 ± 0.0051%, 99.16 ± 0.0012% and 98.69 ± 0.0065%, respectively. Isolate G5 significantly inhibited the formation of conidia of M. oryzae, with an inhibition rate of 97% at an OD600 of 2. Isolate G5 was able to provide 66.81% protection against rice blast under potted conditions. Wholegenome sequencing revealed that the genome size of isolate G5 was 4,065,878 bp, including 4,182 coding genes. Using the anti-SMASH software, 14 secondary metabolite synthesis gene clusters were predicted to encode antifungal substances, such as fengycin, surfactin, and bacilysin. The G5 isolate also contained genes related to plant growth promotion. These findings provide a theoretical basis for expounding the biocontrol mechanisms of this strain and suggest further development of biogenic agents that could effectively inhibit rice blast pathogen growth and reduce crop damage, while being environmentally friendly, conducive to ecological development, and a sustainable alternative to chemical pesticides. This study also enriches the relevant research on endophytes of wild rice, which proves that wild rice is a valuable microbial resource bank.